2018
DOI: 10.1088/1361-6528/aaa64d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical responses ofa-axis GaN nanowires under axial loads

Abstract: Gallium nitride (GaN) nanowires (NWs) hold technological significance as functional components in emergent nano-piezotronics. However, the examination of their mechanical responses, especially the mechanistic understanding of behavior beyond elasticity (at failure) remains limited due to the constraints of in situ experimentation. We therefore performed simulations of the molecular dynamics (MD) of the mechanical behavior of [Formula: see text]-oriented GaN NWs subjected to tension or compression loading until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The authors suggested that the thickness of the oxide coating layer changes by ≈5 nm, the Young's modulus produces 16% change on average, as shown in Figure 6h. [179] From a practical point of view, it is important not only to characterize the mechanical properties of nanowires, but also to examine their dynamic responses, such as elastic-plastic response [183][184][185] and brittle-ductile transition. [186][187][188] An insightful understanding of mechanisms of such mechanical responses is highly demanded to design nanowire-based devices bearing tunable mechanical properties.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The authors suggested that the thickness of the oxide coating layer changes by ≈5 nm, the Young's modulus produces 16% change on average, as shown in Figure 6h. [179] From a practical point of view, it is important not only to characterize the mechanical properties of nanowires, but also to examine their dynamic responses, such as elastic-plastic response [183][184][185] and brittle-ductile transition. [186][187][188] An insightful understanding of mechanisms of such mechanical responses is highly demanded to design nanowire-based devices bearing tunable mechanical properties.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The revenue in the beauty and personal-care business is predicted to reach US$571.10 billion in 2023, with a 3.80% annual rise [3]. Aside from natural ingredients like polyphenols in cosmetics and drugs, two-dimensional (2D) materials have also been added to enhance the efficacy of these personal-care products due to their exceptional physicochemical properties, such as excellent electronic and thermal conductivity, extensive surface area, strong mechanical strength, and impressive optical transmittance [4,5]. Particularly, pristine graphene (PG) and graphene oxide (GO), two prototypes of 2D materials, have long been widely applied in cosmetics, drug delivery, biosensors, optics, and nanocomposites [6][7][8][9], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang et al [18] formulated research with the help of molecular dynamics on B4 ceramic to examine the creation of prismatic loops on it due to nanoindentation. Wang et al [19], after carrying out a study on the mechanical response of the GaN nanowires in their inelastic range, reported that the failure mechanisms are dependent on size and the shuffle set pyramidal planes. Aida et al [20] revealed the relation between depth of the subsurface damage (SSD) and the diamond abrasive size which was used for GaN substrates for mechanical polishing.…”
Section: Introductionmentioning
confidence: 99%